Hubungan Prematuritas dengan Hipotiroid Kongenital - Aprilia, Sandrina Audy; Kurniati, Intanri; Kusumaningtyas, Intan; Berawi, Khairun Nisa (JIMKI: Jurnal Ilmiah Mahasiswa Kedokteran Indonesia, 2025)
Introduction: Congenital hypothyroidism is the most common endocrine disorder in neonates and can cause growth and developmental disorders if not treated early. Prematurity is an important risk factor due to the immaturity of the hypothalamic–pituitary–thyroid axis and limited iodine storage capacity. Various studies have shown an increased risk of congenital hypothyroidism, particularly in its transient form, among preterm infants; however, the results remain variable, necessitating a literature review to clarify the association and optimize detection strategies. Method: This study is a literature review analyzing the relationship between prematurity and congenital hypothyroidism. Literature searches were conducted through PubMed, ScienceDirect, Scopus, Google Scholar, SpringerLink, and Garuda (2015–2025). Included articles consisted of original research, reviews, and meta-analyses in English or Indonesian discussing the topic. Discussion: Prematurity is associated with an increased risk of congenital hypothyroidism, particularly transient forms and delayed TSH elevation. Immaturity of the thyroid axis, exposure to medications, and external factors exacerbate hormonal dysfunction. Most cases are temporary, although a small proportion may become permanent. Conclusion: Prematurity increases the risk of congenital hypothyroidism; therefore, repeated screening and long-term monitoring are essential to prevent delayed diagnosis and ensure optimal management.